Influence of the curvature correction to the surface tension on nuclear fragmentation at intermediate energy head-on heavy ion collisions. (December 2020) - Cherevko, K. V.; Bulavin, L. A.; Sysoev, V. M.
Abstract: Hydrodynamic model of the "doughnut"-like structures formation in the head-on heavy ion collisions at intermediate energies is analyzed. Modification of the model is suggested to include the curvature correction to the surface tension coefficient. It is shown that accounting for the curvature correction changes the overall reaction time, maximum size of the system and the number of fragments. The results obtained show good correspondence with the results of the transport theory calculations and experimental data for the number of fragments and spreading size. The conducted analysis suggests that accounting for the curvature correction to the surface tension coefficient is essential when studying the dynamics of the system in the heavy ion collisions.